MAKNA KONTEKSTUAL â€œSAMARINDA BEBAS TAMBANGâ€ PADA BERITA DARING: KAJIAN EKOLINGUISTIK - Valend Young Wenerlee; Milla Kristina; Ian Wahyuni (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
The purpose of this research is to describe the contextual meaning of some online news on kaltimpost.id and Pojoksatu.id regarding "Samarinda Free of Mining". This research method uses qualitative method and descriptive approach. This type of research is literature, which is research whose data is taken mainly from literature (books, documents, articles, reports, newspapers, and so on). The data in this research are words, phrases, and sentences in online news that discuss "Samarinda Free of Mining". The source of data in this research is online news kaltimpost.id uploaded on April 5, 2023, Pojoksatu.id uploaded on April 3, 2023, and online news mediakaltim.com uploaded on March 20, 2023. The results of research on online news kaltimpost.id, Pojoksatu.id, and mediakaltim.com show that contextual meaning refers to natural damage and disruption of animal ecosystems in the sea and on land due to mining activities.